Palladium and copper complexes based on dendrimeric and monofunctional N, N’ chelating ligands as potential catalysts in the oxidative carbonylation of alcohols - Mketo, Nomvano (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2010.